Cybercounseling: Characteristics and Barriers for Use in School Counseling Programs - Law, Michael B. (Valdosta State University College of Education, 2002)
With the impact of technology, the time has come to address alternative ways to providing counseling by integrating technology and using the Internet as an avenue of counseling. This electronic form of counseling is called cybercounseling. The purpose of this study was to explore counselor knowledge, opinions, ethical concerns, legal concerns, and recommendations for implementation of cybercounseling in the schools and to test a site to see if parents would use the site as a means of counseling and communication with the school counselor. The researcher polled attitudes of practicing school counselors to see what their attitudes were concerning the implementation of cybercounseling in the school setting. The researcher gained insight in how to implement this form of counseling in schools. A pilot website was implemented and advertised to parents soliciting usage from parents and students at a rural, elementary school in Southwest Georgia. The researcher found that little is known about this new innovation and that a number of concerns expressed by the respondents should be explored before the diffusion of this innovation is adopted. Suggestions to aid in narrowing the gap of how to implement this innovation and overcome some evident barriers were offered by certified professional school counselors. The interactive website proved that parents and students would use it if one is made available to them.